PENGARUH KUAT ARUS TIG WELDING PADA MATERIAL SUS 304 TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO - Wahyu Aditya Rohman; Rizal Arifin; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2021)
GTAW welding (gas tungsten arc welding) or commonly called TIG (tungsten inert gas) welding is welding using a flame arc produced by a fixed electrode made of tungsten. One thing that needs to be considered in welding (especially in TIG welding) is the effect of welding amperage on the mechanical properties or strength of the welded joint. PeThe tests carried out in this study were tensile tests and micro tests. Tensile tests were carried out with the aim of knowing the tensile strength of the test specimens. And the micro test is carried out aiming to see the microstructure that occurs in the weld area (HAZ). Data analysis was carried out by looking at the relationship of tensile stress, yield stress, and strain that occurred in the test specimen based on variations or parameters used during welding. Based on the analysis of the mechanical properties and microstructure of thematerial stainless steel sus 304 musing TIG welding (Tungsten Inert Gas)with a current variation of 80 A, 100 A and 120 A showed a difference that caused a comparison of the difference in the tensile strength. Welding using a current of 80 A has the highest average stress of 316.6 kN/mm2, welding using a current of 100 A has a tensile strength of 378.6 kN/mm2. While welding using a current of 120 A has the highest tensile strength of 458.3 kN/mm2. The results of this test indicate that the analysis of the mechanical properties and microstructure of TIG welding (Tungsten Inert Gas) shows a significant effect of tensile strength at a current of 120 A, so it has the highest tensile strength with an average value of 458.3 kN/mm2